Smart Pregnancy Tracker System Using Social Knowledge Networks for Women - Santur, Yunus; Santur, Sinem Guven; Karakose, Mehmet (Ieee, 2017)
Today, people use the internet extensively to meet their information needs, to socialize, to communicate, to handle formal and informal processes. The web-based information networks established for this purpose are growing day by day and reach a larger audience. Facebook, the world's largest social network, has reached 2 billion users. There are social information networks established for different purposes as well. In this study, it was aimed to construct a social information network specific to women. It is to create a social information network specific to women targeted for work. In web-based network working with membership logic, members can access informative contents such as follow-up of processes such as period, pregnancy, baby vaccination schedule, body mass index, calculators such as baby percentile, tests, articles and visual aided trainings.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: big data; elasticsearch; pregnancy tracker; period tracker; social network; web crawlerl